2022
DOI: 10.55519/jamc-04-s4-9714
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Manifestations in Patients With Rheumatoid Arthritis Visiting Tertiary Care Hospital

Abstract: Background: Rheumatoid arthritis is a common problem in elderly individuals. It is reported that lung involvement in these patients is widely present. This study was done with the purpose to assess the burden and characteristics of lung involvement in rheumatoid arthritis patients attending rheumatology clinic. Methods: This descriptive cross-sectional study, in which data was retrospectively collected, was carried out from April 2019 to December 2020 at the Rheumatology Department of Jinnah Postgraduate Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
3
3
Order By: Relevance
“…It is relatively higher compared to previous study by Ahsen et al 15 where patients' satisfaction in regards to cleanliness was only 44% which means that there has been slight improvement in hygiene conditions of the hospital. Our study results are higher than the studies conducted by Kaur et al 16 where it was 46% and by Verma et al 19 where it was 47%.…”
Section: Resultscontrasting
confidence: 67%
See 3 more Smart Citations
“…It is relatively higher compared to previous study by Ahsen et al 15 where patients' satisfaction in regards to cleanliness was only 44% which means that there has been slight improvement in hygiene conditions of the hospital. Our study results are higher than the studies conducted by Kaur et al 16 where it was 46% and by Verma et al 19 where it was 47%.…”
Section: Resultscontrasting
confidence: 67%
“…This included attitude of doctor, explanation of their disease, diagnosis and treatment facility provision. This is higher as compared to previous studies by Ahsen et al 15 where it was 70%, by Verma et al 19 and by Kaur et al 16 where satisfaction was 67% and 78% respectively. It is less compared to study by Paniyadi et al 18 and Pande et al 17 where 94.7% and 97.3% of patients were satisfied with care provision by doctor and explanation of their disease and treatment respectively.…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…Overall satisfaction the study gave good satisfactory result of the respondent experience. (32) Descriptive qualitative study conducted in Mayo hospital reported that 22% parents were fully satis ed while 11% of the parents totally dissatis ed while many of patients were pleased. (42)Our study majority of the study participants showed satisfactory response.…”
Section: Discussionmentioning
confidence: 99%